(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe patient characteristics and evaluate pain; function, and radiographic changes after balloon kyphoplasty for osteoporotic vertebral compression fractures (OVCF). Materials and methods: A pre–post case series of 56 OVCF patients treated at Son La Provincial General Hospital (01/2024–03/2026). Pain and disability were assessed using the Visual Analog Scale (VAS) and Roland–Morris Disability Questionnaire preoperatively, postoperative day 1, month 1, and month 3. Radiographic outcomes included wedge angle, Cobb angle, and vertebral body heights (anterior/middle/posterior). Paired t-tests compared pre–post values (p<0.05). Results: Mean age 69.18±9.33 years; 67.9% female. VAS decreased from 7.61±1.12 preoperatively to 2.73±1.14 (day 1), 1.63±0.84 (month 1), and 1.32±0.86 (month 3) (all p<0.001). Roland–Morris decreased from 17.43±2.20 to 10.39±1.37, 8.75±1.05, and 7.82±0.69 (all p<0.001). Wedge angle improved from 13.26±1.95° to 9.79±1.45°, Cobb angle from 17.97±2.16° to 12.71±1.87°, with significant increases in anterior and middle vertebral heights (all p<0.001). No complications occurred in 82.1%. Cement leakage was observed in 10.7% (anterior border) and 7.1% (intradiscal), all asymptomatic and requiring no intervention. Conclusions: Balloon kyphoplasty provided rapid and sustained pain relief, functional improvement, and meaningful radiographic correction in OVCF, with a low rate of asymptomatic cement leakage, supporting its safety and effectiveness in a provincial hospital setting.